Outcome Evaluation of a Transnational Postgraduate Capacity-Building Program Using the Objective Structured Clinical Examination - Park, Kye-Yeung; Park, Hoon-Ki; Shin, Jwa-Seop; Kim, Taejong; Jung, Youngjoo; Seo, Min Young; Bouphavanh, Ketsomsouk; Sengchanh, Sourideth; Inthachack, Ketmany (Evaluation review, 2023)
Previous studies have applied interview-oriented self-reported or peer-centered evaluation methods, rather than an objective and quantitative method, to evaluate outcome of a postgraduate capacity-building program and have mainly focused on the cognitive level. To investigate the feasibility of the objective structured clinical examination (OSCE) in an international setting and report the results of the outcome evaluation for the behavioral aspect. A case–control study. Ninety examinees divided into 2 case–control groups: 17 program-experienced doctors and 17 control doctors in the first group, and 28 mentees of the program-experienced doctors and 28 control doctors in the second group. A six-station OSCE was implemented. The OSCE scores were measured to evaluate (1) the direct educational effect regarding learning in the first group and (2) the indirect educational effects regarding transfer in the second group. Written questionnaire and interview data were collected for qualitative analysis. The quantitative results of the overall or subcomponent OSCE scores indicated no significant differences in the comparisons of the first and second case-control groups. The qualitative data indicated that the program improved participants’ medical knowledge, skills, and self-confidence, however, it also revealed limited learning environment provided by the program. This transnational study has demonstrated the process for introducing and successfully completing the testing of an OSCE in Laos. Discrepancy in the goals of the OSCE and the education program limited the usefulness of OSCE as an assessment tool, leading to the lack of significant differences in its results.